2020
DOI: 10.1155/2020/9796419
|View full text |Cite
|
Sign up to set email alerts
|

Preoperative Altered Spontaneous Brain Activity and Functional Connectivity Were Independent Risk Factors for Delayed Neurocognitive Recovery in Older Adults Undergoing Noncardiac Surgery

Abstract: Objectives. Recently, it has been demonstrated that patients with subtle preexisting cognitive impairment were susceptible to delayed neurocognitive recovery (DNR). This present study investigated whether preoperative alterations in gray matter volume, spontaneous activity, or functional connectivity (FC) were associated with DNR. Methods. This was a nested case-control study of older adults (≥60 years) undergoing noncardiac surgery. All patients received MRI scan at least 1 day prior to surgery. Cognitive fun… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
3

Relationship

2
1

Authors

Journals

citations
Cited by 3 publications
(8 citation statements)
references
References 52 publications
0
8
0
Order By: Relevance
“…The abnormal alterations in FC of calcarine were related to cognitive impairment (Moon and Jeong, 2017). In a previous study, we also found that altered preoperative FC of calcarine was independently associated with the occurrence of DNR (Jiang et al, 2020). The DSST and TMT-A neurocognitive tests were employed to assess the visual-related cognitive function (Joy et al, 2003;Llinàs-Reglà et al, 2017).…”
Section: Discussionmentioning
confidence: 93%
See 4 more Smart Citations
“…The abnormal alterations in FC of calcarine were related to cognitive impairment (Moon and Jeong, 2017). In a previous study, we also found that altered preoperative FC of calcarine was independently associated with the occurrence of DNR (Jiang et al, 2020). The DSST and TMT-A neurocognitive tests were employed to assess the visual-related cognitive function (Joy et al, 2003;Llinàs-Reglà et al, 2017).…”
Section: Discussionmentioning
confidence: 93%
“…The inclusion and exclusion criteria of our study population have been described previously ( Jiang et al, 2020 ). The inclusion criteria included patients scheduled to undergo non-cardiac surgery, age ≥ 60-years-old, American Society of Anesthesiologists (ASA) classification I-III, and right handedness.…”
Section: Methodsmentioning
confidence: 99%
See 3 more Smart Citations